(untitled) (Global Journal of Management and Business Research, 2012)
SME buyers tend to avoid formal binding contractual arrangements with suppliers of resources, a situation which creates operational and technical difficulties and increases transactional costs. Ntayi et al., 2010a using data from Ugandan SMEs have revealed that majority of buyers (83.4%) use oral agreements in their business transactions with suppliers. Only a few (16.6%) were observed to have used written contracts. Whereas informal and oral contracts are enforceable in the Uganda#x2019;s commercial court, the process of assembling evidence is tedious and takes long (Kiryabwire, 2010). In such circumstances parties privy to the contract end up losing genuine cases unfairly. Even where they are successful, the assessment of damages to be awarded to the victor is a nightmare as business records are non-existent to properly establish the impact of the breach of contract on the business (Kiryabwire, 2010). This happens in SME business relationships which are meant to generate intangible and tangible benefits in short or long terms through the firm#x2019;s social capital. The purpose of this study is to examine the effects of social capital, organizational amnesia, and moral reasoning on the enforcement behaviors of informal contracts in Ugandan SMEs. This study adopts a triangulation approach and collects data from a sample of 2,228 SMEs. Results reveal that social capital and organizational amnesia have a significant negative effect on the enforcement behavior of Ugandan buyer-supplier informal contracts. However, the interactive effects of: social capital and moral reasoning; and organizational amnesia and moral reasoning has a positive effect on the enforcement behavior of Ugandan buyer-supplier informal contracts. This has policy and managerial implications which we present and discuss in our paper.